Investigating the biosynthetic mechanisms of the brevianamides & penicimutamides through the total synthesis of secondary metabolites - McCauley, Morgan Taylor, author; Bandar, Jeff, advisor; Kennan, Alan, committee member; Szamel, Grzegorz, committee member; Slayden, Richard, committee member (Colorado State University. Libraries, 2020)
The class of prenylated indole alkaloids containing a bicyclo[2.2.2]diazaoctane ring system consists of secondary metabolites isolated from fungal genera that possess diverse biological activities. Recent findings have established three ways in which the bicyclic core in this class can be constructed: (1) Generation of the monoxopiperazines (malbrancheamides and related families) by an NADPH-dependent bi-functional reductase/Diels-Alderase; (2) An enantiodivergent generation of the dioxopiperazines by some cytochrome P450 creation of achiral azadienes and successive enzyme-mediated stereoselective intramolecular hetero-Diels-Alder (IMDA) reaction in the notoamide/stephacidin families; and (3): non-Diels-Alderase generation of the bicycle of the brevianamides directed by a novel cofactor-independent pinacolase, culminating in a spontaneous IMDA reaction. The goal of the current work was to employ total synthesis to assist with the full characterization of unknown metabolites and decipher biochemical mechanisms employed in fungal organisms. Through this, the first total synthesis of brevianamide X and penicimutamide E, along with the synthesis of brevianamide A, and an improved, enantioselective synthesis of brevianamide Y were completed. The details of the novel synthetic work carried out by the author can be found in Chapters 3 and 5. Further synthetic efforts to better understand and access a variety of natural products are in progress to decipher the intrinsic transformations organism found in nature harness.
Keywords: prenylated indole alkaloids; natural products; total synthesis